'Because I Don't know': uncertainty and ambiguity in closed-ended reports of perceived discrimination in US health care. Issue 5 (3rd September 2017) - Irby-Shasanmi, Amy; Leech, Tamara G.J.
ABSTRACT: Objective: Surveys often ask respondents to assess discrimination in health care. Yet, patients' responses to one type of widely used measure of discrimination (single-item, personally mediated) tend to reveal prevalence rates lower than observational studies would suggest. This study examines the meaning behind respondents' closed-ended self-reports on this specific type of measure, paying special attention to the frameworks and references used within the medical setting. Design: Twenty-nine respondents participated in this study. They were asked the widely used question: 'Within the past 12 months, when seeking health care do you feel your experiences were worse than, the same as, or better than people of other races?' We then conducted qualitative interviews focusing on their chosen response and past experiences. Descriptive analyses focus on both the quantitative and qualitative data, including a comparison of conveyed perceived discrimination according to the different sources of data. Results: To identify discrimination, respondents drew upon observations of dynamics in the waiting room or the health providers' communication style. Our respondents were frequently ambivalent and uncertain about how their personal treatment in health care compared to people of other races. When participants were unable to make observable comparisons, they tended to assume equal treatment and report 'same as' in the close-ended reports. Conclusion: Respondents' responses to single-item, closed-ended questions may be influenced by characteristics specific to the health care realm. An emphasis on privacy and assumptions about the health care field (both authority and benevolence of providers) may limit opportunities for comparison and result in assumptions of racial parity in treatment.